(untitled) (Siddhajyoti Interdisciplinary Journal, 2023)
This study explored the gender roles of text characters and the messages given at grade three and four social studies textbooks of the community school of Nepal.The study further explored the gender representations of text characters in the textbooks through exploratory qualitative method; the verbal data noted from the textbooks were analysed through content analysis. The textbooks of grade three and four social studies were purposively selected because they have recently been reconstructed. The major findings are that the textbooks are the depiction of patriarchal traditional gender bias mind-sets and the dominance of men over women. Men and women are portrayed in traditional gender bias occupations: strong, prestigious, intelligent and leading works are provided to male characters, and weak, subsidiary, subordinate, less prestigious and household chores are determined to women in the textbooks. The male-dominated family structures portrayed in the textbooks may not eliminate gender inequality, and reinforce male-dominated society in Nepal. Curriculum designers and textbook writers must reconsider the equal gender representations in the children’s textbooks to construct a positive effect on children’s gender perceptions while revising and/or producing new textbooks in future.